Prevalence of BRCA1 Oncogen Expression in Breast Cancer Specimens of Patients with Positive Family History - Al- Dabbagh, Wijdan. H.; Al- Alwan, Nada. A.S.; Al-Aubaidy, Salim R. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Breast cancer is the leading female cancer worldwide and in Iraq .Some mutations, particularly in BRCA1, significantly increase the risk of the disease. Objectives: To demonstrate the frequency of BRCA1 in a group of high risk women with “positive family history’’ of breast cancer; correlating the immune expression of BRCA1 with some parameters of known prognostic significance. Patients and Methods: Eighty-two female patients diagnosed with breast cancer (50 familial and 32 non familial) were included in the study .The mean age of the patients was 48.07. Immunohistochemistry was performed to assess the BRCA1 oncogene expression, Estrogen Receptor (ER), Progesterone Receptor (PR), Her 2 neu contents of the tumors. Results: Out of the study group, 60.9% revealed family history of breast cancer. Forty-eight percent of the patients with positive family history were in the age group of 45 years or below; of those, 42.9% gave family history of cancer in their first degree relative while 25.7% had second degree relatives. BRCA1 positive expression was demonstrated in 39.02% out of all patients with breast carcinoma. In patients with positive family history for breast carcinoma, BRCA1 positive expression was demonstrated in 54% while in patients with negative family history it was 15.6%. Among patients with positive BRCA1 expression 71.9% of those had negative ER expression and 57.9% exhibited negative PR expression. Conclusions: BRCA1 gene expression determination in patients with positive family history should be promoted and validated to serve as indicators for early diagnosis of the disease.